UTILIZATION OF MOLECULAR MARKER TECHNOLOGY IN FOXTAIL MILLET (Setaria italica (L.) P. Beauv.) BREEDING IN INDONESIA - Ramlah Ramlah (Universitas Sulawesi Barat, 2021)
Efforts to increase the productivity and quality of foxtail millet (Setaria italica (L.) P.Beauv.) to supporting domestic food diversification in Indonesia can be done through plant breeding programs by assembling superior varieties. The effort to obtain superior millet varieties that are specific in accordance with farmer wishes, requires the availability of informative germplasm, which is delivered through characterization activities. The use of molecular markers is a method that now has been proven to help accelerate the introgression of major genes into elite cultivars. The use of molecular markers as a plant selection tool has been carried out with greater accuracy. Selection with molecular markers is only based on plant genetic traits and is not influenced by environmental factors, so the results are more accurate than selection based on morphology. Molecular tests have vary in the way they are implemented to obtain data, both the technique and the desired level of target data, according to the ease of implementation, availability of human resources, facilities and funds of money. The molecular markers that have been used for plant breeding of foxtail millet are RFLP, AFLP, RAPD, Transposon, SSR-Microsatelite, and ISSR.